A study of the swell-shrink behavior of expansive Moreland clay. Issue 3 (4th May 2019) - Khan, Md Adnan; Wang, Jay X.; Patterson, William B.
Abstract: Understanding expansive soil has always been a major challenge for soil scientists and engineers. Due to the presence of high quantity of montmorillonite mineral in the northern Louisiana's Moreland clay, structural damage due to soil heave was a key concern for geotechnical engineers. In this paper, a state-of-the-art characterization of the Moreland clay is presented. It includes the identification of its swell-shrink properties, soil index property measurements, attainment of the soil water characteristics curve (SWCC), development of an empirical equation for its unsaturated shear strength, establishment of its 3-D constitutive surface, and the soil heave predictions. Atterberg limits of the soil samples from the typical Moreland clay site were obtained, with a liquid limit (LL) of 79, a plasticity index (PI) of 51 and an activity (AC ) of 1.3. The characterization is to gain for the first time a clear understanding of the volume change behaviors of the expansive clay.